Learning Endotracheal Tube and Laryngeal Mask Airway Intubation with Android Applications for Nursing Students - Catur Budi Susilo; Pramadita Elena; Furaida Khasanah (JURNAL INFO KESEHATAN, 2025)
E-learning in anesthesiology nursing faces challenges like finding practice materials, mastering ETT and LMA techniques, and tool damage. This research aims to develop an android application model to support valid and effective learning for endotracheal tube and laryngeal mask airway intubation for nursing students.This research uses Research and Development (R&D) method with the 4D model by Thiagarajan and just untill a limited group trial. Quantitative method of data collection techniques using a questionnaire. Questionnaire given to material experts and media experts to test product eligibility and use of knowledge questionnaires as well and also System Usability Scale for students to test the effectiveness and acceptance. Result of this research show that the material experts assessment was 92.00% which was classified as very feasible and media experts was 98.52% which was classified as very feasible. Results of pretest and posttest analyzed by wilcoxon test from 34 students obtained results of 0.000 which were significant as well. System Usability Scale result was 85.66 classified acceptable with adjective rating B or good. This Android- based application is very feasible and can be used as a support for learning on the topic or material for ETT intubation and LMA intubation.